(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
There are non-utilized silent professional skills encapsulated in Mechanical Technology Education (MTE). These skills when harnessed and develop, have the capacity of launching Vocational and Technical Education (VTE) students into private enterprise ventures upon graduation. Hence, the purpose of this study was professional skills in Mechanical Technology for VTE students’ private enterprise development after school. To achieve the objective of the study, a descriptive survey design was adopted. A total population of 45 respondents (20-MTE lecturers and 25-Mechanical Engineering Industry Practitioners (MEIP)) was used for the study. There was no sampling. Four specific purposes and Research Questions (RQs) guided the study. The only data collection instrument for the study was the: “Professional Skills in Mechanical Technology Education Questionnaire™ (PSMTEQ). The PSMTEQ was face validated by three experts. Cronbach Alpha Coefficient method was used to establish the reliability coefficient index for the MTE professional skills as follows: Engineering Drawing (0.89), Refrigeration and Air-Conditioning (0.87), Machine Tools Processing (0.81), Motor Vehicle Repair (0.90); and the entire instrument (0.87). The four stated RQs were analyzed using Mean, and Standard Deviation. The study found sixty-eight professional skills in Mechanical Technology for VTE students in private enterprise development after school. Therefore, the study recommended among others, that to maximize the full benefits of this study, the identified skills should be developed into practical entrepreneurship development programs to be followed in higher VTE institutions to teach students skills for self-reliance in private enterprising ventures. With this, graduates of MTE will be aware of the several skill options available in their chosen careers.